Retrospective investigation of antibodies against chikungunya virus (CHIKV) in serum from febrile patients in Mozambique, 2009–2015: Implications for its prevention and control - Antonio, Virgilio Santo (PLoS One, 2019)
INTRODUCTION: Longitudinal data and trends about chikungunya virus (CHIKV) are critical for its control, however in Mozambique very few studies were conducted over 5 decades, between 1957 and 2013. In this study, we retrospectively investigated the occurrence, geographical distribution and trend of anti-CHIKV antibodies between 2009 and 2015 in Mozambique using serum samples from febrile patients. METHODS: A total of 895 serum samples collected from febrile patients for measles and rubella surveillance between 2009 and 2015 in 127 districts of Mozambique were retrospectively tested for IgM and IgG antibodies against CHIKV using a commercially available ELISA. RESULTS: The median age of patients was 2 years (IQR: 1–5 years) and 44.2% (395/895) of them were female. We found that 54 (6.0%) of samples were positive for anti-IgM chikungunya, and 160 (17.9%) were positive for anti-CHIKV IgG. Antibodies against CHIKV (IgM and IgG) were identified in serum throughout 2009 to 2015. While frequency of IgG antibodies was significantly higher in 2015 as compared to other years, frequency of IgM antibodies was homogeneous between 2009 and 2015. Antibodies against CHIKV were reported in all provinces and in 84 (66.1%) of the districts studied. Frequency of IgM and IgG antibodies was not significantly similar between age groups. CONCLUSION: This is the largest and longest serological screening of antibodies against CHIKV in febrile patients in Mozambique and findings from this study suggest that Mozambicans from all over the country have been silently exposed to CHIKV for several years.